An Analysis on Classroom Management Applied by the English Teachers - Nova Pandan Sari; Wisma Yunita; Kasmaini Kasmaini (Universitas Bengkulu, 2021)
This research was aimed to find out the components of classroom management applied by the two English teachers of SMA Negeri 05 Kota Bengkulu and. This study used descriptive quantitative method. The data were collected by using the observation checklist and video recording and the data were analyzed by using four procedures by Nurjanah and Maemunah namely identifying and classifying the data, investigating the data and analyzing the data. The result of this research revealed that, there were 4 of 5 components applied by the teachers A in managing the class; 1) Physical presence, 2) Teacher’s voice, 3) Teacher talking time, and 4) Student’s grouping. Meanwhile, the student’s seating arrangement component did not apply by the teacher A. In addition, there were 3 of 5 components applied by the teacher B such as; 1) Physical presence, 2) Teacher’s voice, and 3) Teacher talking time. Meanwhile, student’s seating arrangement and student’s grouping did not apply by the teacher B. Therefore, it can be concluded that the classroom management applied by the English teachers of SMA Negeri 5 was less variative since the teachers did not apply all components on classroom management.